Die Entwicklungslogik der nominalen Determinativkomposition im Deutschen – verstanden als Grammatikalisierung - Werner, Martina (Linguistik Online, 2016)
Under the assumption of an individually grammatical semantics of word-formation types, this paper deals with the development of determinative compounding in the history of German from an inner-morphological perspective. Diachronically, the former research observed that German nouns have become “longer”, i. e. more complex (firstly been formulated by Wurzel 1996). Additionally, some morphological restrictions within nominal compounding have been documented for historical stages of German, but some of them cannot be attested in present-day German. This suggests a formally and semantically motivated, inner-morphological change which can be described in terms of grammaticalization theory. For this purpose, previ-ous results from historical word-formation and semantics will be combined with new observa-tions on morphological discontinuities in the history of German, especially by focussing on morphological restrictions from a synchronic and a diachronic perspective. Since this approach comprises various linguistic phenomena (such as the diachronic development of part of speeches, (de-)referencialization, definiteness etc.) and since morphological restrictions have merely not been documented empirically – neither for present-day nor for historical stages of German, the paper aims at sketching the most prominent lines of development from a theoreti-cal perspective, also by contrasting them with results from language typology, variational lin-guistics, and semantics. Additionally, the paper provides morpho-syntactical prospects for further theoretical and empirical research on historical morphology, also by conceiving word-internal language change as an integral part of the dynamics of morpho-syntactic structuring.